Computational simulation of flow-induced arterial remodeling of the pancreaticoduodenal arcade associated with celiac artery stenosis - Yuhn, Changyoung; Hoshina, Katsuyuki; Miyahara, Kazuhiro; Oshima, Marie (Journal of biomechanics, 2019)
Arterial remodeling of the pancreaticoduodenal arcade, which enables collateral flow to the liver, spleen, and stomach, is a well-recognized clinical sign of celiac artery (CA) stenosis. However, the hemodynamic changes due to remodeling are poorly understood, despite their importance in surgical procedures such as pancreaticoduodenectomy. In this study, a framework to simulate remodeling of the arterial network following pathological flow alterations was developed and applied to investigate the hemodynamic characteristics of patients with CA stenosis. A one-dimensional–zero-dimensional cardiovascular model was used for blood flow simulation. After introducing CA stenosis into the normal network, arterial remodeling was simulated by iteratively changing the diameter of each artery until time-averaged wall shear stress reached its value under normal conditions. A representative case was simulated to validate the present framework, followed by simulation cases to investigate the impact of stenosis severity on remodeling outcome. A markedly dilated arcade was observed whose diameter agreed well with the corresponding values measured in subjects with CA stenosis, confirming the ability of the framework to predict arterial remodeling. A series of simulations clarified how the geometry and hemodynamics after remodeling change with stenosis severity. In particular, the arterial remodeling and resulting blood flow redistribution were found to maintain adequate organ blood supply regardless of stenosis severity. Furthermore, it was suggested that flow conditions in patients with CA stenosis could be estimated from geometric factors, namely, stenosis severity and arcade diameter, which can be preoperatively and non-invasively measured using diagnostic medical images.